Pengembangan Website Carrd.Co Sebagai Media Pembelajaran Keterampilan Membaca Pemahaman Bahasa Jerman Siswa SMA Kelas XI - Purnomo, Fitri Novitasari; Wahyuningsih, Fahmi (LATERNE, 2025)
Carrd.Co is a platform for creating websites that does not require complex programming languages and can be customized to be attractive. Carrd.Co can be used as one of the alternative media for learning German. The background of this research is the low reading ability of students is caused by the lack of variety in learning media. The formulation of the problem in this study is how the process of developing the Carrd.Co website into a learning medi a for reading comprehension skills of German language high school students, grade XI. This research aims to find out the process of developing the Carrd.Co website as a learning media for reading comprehension of German language for XI grade high school students. The research method used is Research and Development with Bergman and Moore's development model (1990) which has 6 stages, namely needs analysis, design, production development, incorporation, validation. The results of material validation received a score of 88.5% which was declared very feasible to use. Then the results of media validation get a final score of 89% which means that the Carrd.Co website media is very feasible to use as a German language learning media